Teachers' Perception in Teaching Large Class Sizes at Undergraduate First Year Regular Students in Some Selected Private and Public Higher Learning Institutions in Eastern Ethiopia and Its Implication on Quality Education - Gobena, Gemechu Abera (Journal of Education and Practice, 2014)
This study was designed to investigate the perception of teachers towards teaching large class sizes as prevalent in some selected Eastern Ethiopian Higher Learning Institutions today due to the present social demand for education. The samples used for the study were 211 teachers randomly selected among both Private and Public Higher Learning Institutions in Eastern Ethiopia. The instrument used for this study was Questionnaire and unstructured observational checklist which were used for the collection of data and then analyzed using frequency count, percentage, mean score, standard deviation and One Way ANOVA statistical tools in the former one. The findings revealed that the teachers were not favorably contented to teach large class sizes. The majority were of the view that in such class sizes, it is difficult to engage in practical work; there was less concentration on the part of the students; teaching is teacher–centered; the level of students’ participation is low and there are heavier demands on facilities and instructional materials. The study further revealed that teachers have the attitude that coping strategies such as peer tutoring and instructor – expressiveness and teaching behavior can be employed by them to assure quality in teaching and learning in these institutions. The study also indicated that there was no significant mean difference between male and female teachers’ disposition; moreover, it was also found that there was statistically no significant mean difference between more experienced and less experienced teachers’ dispositions. The implication of this study is that teaching large class sizes shows negative impact on the quality of learning by the students but can, however be reduced by concerted efforts to employ suitable teaching methods on the part of teachers. Key words: Class sizes, Haramaya, Private and Public Higher Learning Institution
Keywords: openalex:import

A Comparative study on the Effect of Family Socio- Economic Status between Female and Male Students' Academic Achievement in College of Education and Behavioural Sciences and Haramaya University, Eastern Ethiopia - Gobena, Gemechu Abera (2014)
The main purpose of this study was to assess the comparative effect of family socioeconomic status on students’ (both female and male) academic achievements in one public universityHaramaya University, and College of Education and Behavioural Sciences in Eastern Ethiopia. The target population of the study comprised of four departments namely Adult Education and Community development (AECD), Educational Planning and Management (EdPM), Psychology and Special Needs and Inclusive Education of undergraduate students of 2014 academic year. A sample of these four departments was randomly selected based on sex. The research specific objectives were to establish the extent to which the family socioeconomic status in general and the family income in particular contribute to students’ academic achievement in College of Education and Behavioral Sciences, Haramaya University, Eastern Ethiopia. Descriptive survey research design was employed in carrying out this study. The questionnaire was used to collect data in this study with a sample population of 172 consisting of 85 female and 87 male students from the total of 248 students who were in first year to second year by using stratified random sampling techniques. Data was analyzed using quantitative and qualitative techniques. Quantitative data was analyzed using statistical package for social sciences (SPSS-version 16) whereas qualitative data was sorted out according to the research themes. The study findings indicate that the family income had not brought any significant effect on students’ academic achievement in the subject under study. The findings also showed that there was no statistically significant relationship between Total Family Income per Month (TFIPM) and student academic achievement, (n= 172, r =0.07), p > 0.01, two-tailed. However, it was shown that there was statistically significant negative relationship between sex and students academic achievement, (n=172, r = -0.37), P< 0.01, two-tailed. Moreover the stepwise multiple regression coefficient analysis indicated that 89% and 86% respectively of the influence of students’ academic achievement were not from educated and non educated family’s contribution as indicated by coefficients of determinations (1-R 2 ). The study finally recommended that there needed to be enhancing the adult education for families to enable them caters for education needs of their children. This can be done by enabling families’ access to educations so as to encourage their children in any level of education.
Keywords: openalex:import